2011
DOI: 10.5021/ad.2011.23.3.342
|View full text |Cite
|
Sign up to set email alerts
|

Parry-Romberg Syndrome with En Coup de Sabre

Abstract: Parry-Romberg syndrome (PRS) is a relatively rare degenerative disorder that is poorly understood. PRS is characterized by slowly progressing atrophy affecting one side of the face, and is frequently associated with localized scleroderma, especially linear scleroderma, which is known as en coup de sabre. This is a report of the author's experiences with PRS accompanying en coup de sabre, and a review of the ongoing considerable debate associated with these two entities. Case 1 was a 37-year-old woman who had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
(26 reference statements)
1
32
0
4
Order By: Relevance
“…Mazzeo, et al irst reported this syndrome with root atrophy of maxillary and mandibular teeth and pulp stones in irst permanent molars [16]. This patients had the mentioned manifestations and also other various manifestations reported in previous literatures [3,5,10,11,15,16,25,27]. On the affected side, teeth was hypoplastic and had normal morphology but with smaller size.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Mazzeo, et al irst reported this syndrome with root atrophy of maxillary and mandibular teeth and pulp stones in irst permanent molars [16]. This patients had the mentioned manifestations and also other various manifestations reported in previous literatures [3,5,10,11,15,16,25,27]. On the affected side, teeth was hypoplastic and had normal morphology but with smaller size.…”
Section: Discussionsupporting
confidence: 57%
“…Most of the patients can bene it from conservative treatments. Treatments vary from prescribing local or systemic anti-in lammatory drugs to reconstructive and orthognathic surgeries [10,25]. In this paper, we have reported a moderate case of Parry-Romberg syndrome, with no familial history of any syndromes.…”
Section: Introductionmentioning
confidence: 81%
“…In the differential diagnosis, the firstly considered disease is progressive hemifacial atrophy (Parry-Romberg syndrome) characterized by progressive hemifacial atrophy without cutaneous sclerosis [8]. However, many authors believe that both diseases are different clinical variants of the same disease [9]. Additionally, LSCS and Parry-Romberg syndrome coexist in 20-37% of the patients with LSCS diagnosis, and both conditions have similar age of onset and disease course [4].…”
Section: Discussionmentioning
confidence: 99%
“…They pointed out the lack of sufficient literature regarding efficacy and safety of steroids and other drugs used to treat the syndrome. [1920]…”
Section: Discussionmentioning
confidence: 99%